Characteristics of Brown Rive var. Inpari 43 and Sonication Treatments for Extraction of Phenolic and Flavonoid Contents - Hadi Munarko; Slamet Budijanto; Azis Boing Sitanggang; Feri Kusnandar (Future Science)
This study aimed to characterize brown rice grain var. Inpari 43 and evaluate the effect of sonication time on total phenolic and flavonoid content. The result showed that Inpari 43 is classified as medium and slender grain which contains about 12% of moisture content. Maceration method was suitable for brown rice flour extraction. It accumulated 65–70 mg GAE/100g and 13–18 mg QE/100g of total phenolic content and flavonoid content, respectively, during 10 to 30 minutes extraction. The pearson correlation analysis indicated a strong positive correlation between extraction time and phenolic and flavonoid content. In conclusion, maceration for 30 minutes accumulates the highest phenolic and flavonoid content in brown rice flour var. Inpari 43.